Customer Perceived Value for Self-designed Personalised Products Made Using Additive Manufacturing - Ikhwan Abdul Kudus, Syahibudil; Campbell, R. Ian; Bibb, Richard (International Journal of Industrial Engineering and Management, 2016)
As end-users become more involved in personalising designs, Additive Manufacturing (AM also known as 3D printing) has become an enabler to deliver this service through the manipulation of three-dimensional designs using easy-to-use design toolkits. Consequently, end-users are able to fabricate their personalised designs through various types of AM systems. This study employs an experimental method to investigate end-users’ reflections on the value of 3D Printed personalised product designs based on Product Value and Experiential Value. The results suggest that end-users gave higher value to all measurements for the 3D printed personalised products. This indicates that 3D printed personalised products have increased perceived value when compared to standard mass-production counterparts. Article history: Received (07.11.2016); Revised (21.11.2016); Accepted (20.12.2016)